Figueiredo, Luciano. O avesso da memória: cotidiano e trabalho da mulher em Minas Gerais no século XVIII. Rio de Janeiro, José Olyrnpio; Brasília, DF, EDUMB, 1993. 249p. - Reis, Adriana Dantas (Afro-Ásia, 1997)
.